Peran Komunikasi Interpersonal Ibu Single Parent dalam Perkembangan Kepribadian Anak - Robbi Fauzi, Dedi M (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to examine the role of interpersonal communication among single mothers in shaping children's personalities in Karawang Regency. The background to this research is the high divorce rate and the increasing number of single families, particularly those headed by mothers, who face economic, social, and psychological challenges. The study used a descriptive qualitative approach with a constructivist paradigm to understand the meaning and experiences of mothers in their daily interactions with their children. Data were obtained through interviews, observations, and documentation, then analyzed using the Miles and Huberman interactive analysis model. The results indicate that warm, open, and consistent interpersonal communication between single mothers and their children plays a crucial role in shaping children's personalities, including the values ​​of honesty, responsibility, empathy, discipline, and self-confidence. This interaction encompasses not only the exchange of information but also communication symbols reflecting affection, support, and role modeling. Despite time constraints and the dual burden, mothers successfully create quality communication that supports their children's emotional and social development.   Keywords: Single Parent Mother, Interpersonal Communication, Child Personality, Single Family